Avaliação econômica da produção de leite na agricultura familiar, a partir da alimentação dos bovinos com farelo de soja por prensa extrusora a frio. - Duminelli, Cássio Renê (2015)
This paper explores the experience of Agroenergy aiming at the project feasibility. As for the practical focus, the work includes, specifically, the development of one or more ways to show that Agroenergy jobs are viable in the family farming and just require further exploration. It also seeks to display the different forms of necessary costs to determine the cost of production, showing how the rural manager should behave before purchasing any machine or equipment. The accounting can play an important role as a management tool, through information that enable the planning, control and decision making, turning farms into companies with the ability of following developments in the area, especially concerning the objectives and tasks of the financial management, cost control, crop diversification and comparison of results. Rural businesses, especially small and medium ones, structure themselves in a familial way. Thus, the property owner is also the manager. The chosen study area was the city of São Miguel do Iguaçu - PR, more precisely, the district of Aurora do Iguaçu, located on Guanabara Street, the property of Mr. Marcos Antonio Albino and Mrs. Marizete Aparecida Ben Albino. Lying 9.9 km away from the city of São Miguel do Iguaçu - PR and 6.9 km away from the district of Aurora do Iguaçu, the property has 11.1 hectares or 4,586 bushels. Semiintegral extruded soybean meal, excellent alternative to dairy and beef cattle, pig and poultry farming, etc. High productivity, product with 48% of protein (ms) 6-8% of energy, good incorporation, best benefit-cost ratio. Longer durability of the final product. The alimentation of the bovine with soybean meal replacing the feed used by milk producers, within a period of fifteen (15) days, comparing 8 cows, 4 using the bran produced at Unioeste.